Biotratamento de efluente contaminado por hidrocarbonetos de petróleo - Vieira, Patrícia Angélica (2008)
The present work evaluated the capacity of biodegradation of hydrocarbons present in contaminated effluent for diesel oil and gasoline, using pures (Pseudomonas aeruginosa ATCC 10145, Pseudomonas aeruginosa ATCC 9027, Pseudomonas aeruginosa PATC) and mixed cultures (C1). After the adaptation of these cultures in contaminated effluent (with correction in the phosphorous and nitrogen concentrations) was accomplished the biodegradation kinetic, during 42 days of process. The results of the kinetics showed, that the cultures C1 and the Pseudomonas aeruginosa ATCC 10145 showed higher biodegradation potential in relation to the answer TPH removal. Aiming to reduce the operational costs was accomplished the substitution of yeast extract for autolyzed brewery yeast (ABY) for the two selected cultures and the results showed, that the substituition didn't provide damages in the TPH removal. Aiming to optimize and to verify the influence of the variables nitrogen, phosphorous and inoculum concentrations in the answer TPH removal, a central composite design was used (CCD), employing the culture C1. The optimized nutrients and inoculum concentrations provided TPH removals of 71,5%, after 3 days of process. In this same condition, the results chromatographic showed the following values of degradation of the identified hydrocarbons, in %: 87,1 for the paraffinics, 77,7 for the isoparaffinics, 78,6 for the olefinics, 38,4 for the naftenics and 71,7 for the aromatics. Later, the second central composite design (CCD) was accomplished, aiming to optimize and to verify the influence of the aeration interval and the agitation level in the answer TPH removal. The optimized conditions provided TPH removal of 75,9%, after 3 days of process. And the chromatographic results showed the following results of degradations of the classes of identified hydrocarbons, in % of : 91,8 for the paraffinics, 83,3 for the isoparaffinics, 80,9 for the olefinics, 39,3 for the naftenics and 80,9 for the aromatics. In the last stage of the work was accomplished the comparative study of the process of biodegradation of the contaminated effluent under the conditions with constant aeration (CA), without aeration (WA) and intermittent aeration (IA). The results showed, that the condition IA presented the best results of TPH removals, during 22 days of process, following by the condition CA and WA. For the condition IA was verified at the end of 22 days of process a TPH removal of 90%. And the results chromatographic after the 22 days of process, showed the following values of degradation of the identified hydrocarbons, in % of: 99,6 for the paraffinics, 94 for the isoparaffinics, 95,4 for the olefinics, 70,8 for the naftenics and 83,4 for the aromatics. Through the obtained results can be observed, that this work got to provide an evolution in the increase of the TPH removal, after the optimization of the process operational conditions, using the mixed culture. This evolution, often, it is not verified in several scientific works, because of the mistakes committed during the adaptation stage of the cultures to the contaminated effluent. After all, this stage is crucial for the selection of the most resistant microorganisms and with larger metabolic capacity to biodegradate the pollutants. For this, is necessary to establish with criterion the operational conditions of this stage, that it will be responsible for the sustentation for the subsequent studies.